Implementasi Spiral Dalam Mengembangkan E-Custom Untuk Monitoring Layanan Jual Beli dan Produksi - Saepul Bahri; Lalu Mutawalli; Mohammad Taufan Asri Zaen (STMIK Budi Darma, 2023)
Online-based sales are a must-have for every Micro, Small and Medium Enterprises (MSMEs). By making buying and selling transactions online, business people are no longer need to waste a lot of time for marketing products or services to the marketplace. Considering that there is no current sales system or profile that introduces the sasambo techno company, this research raises a case of study for developing e-custom with a fast and adequate system release in a short time. The problem in this research is the limited time which is very short, therefore this research proposes the spiral method as a methodology for modeling the problems that occur in Sasambo Techno companies and solutions for developing e-custom systems at Sasambo Techno companies as a solution to problems found when conduct research. The spiral model is an iterative system development method that focuses more on risk analysis that will occur when developing the system, risks that will occur to the system and customer requests for the system to be developed. Based on the results of testing the system functionally using a black box which aims to determine the feasibility of the e-custom system when making custom clothing transactions at the Sasambo Techno Company